Different Stages of Entrepreneurship: Lessons from the Transtheoretical Model of Change - Klonek, Florian; Isidor, R.; Kauffeld, S. (Routledge, 2015)
The present study investigates whether the assumptions of the Transtheoretical Model (TTM) can be used as a framework to describe psychological change processes relevant to potential and active entrepreneurs. A sample of 820 participants completed an online questionnaire assessing stages of change (SOC), costs and benefits of entrepreneurship (decisional balance), entrepreneurial self-efficacy, and the steps they have made towards entrepreneurship. The benefits of entrepreneurship, self-efficacy, and entrepreneurial behaviour increased systematically along the SOC. Costs did not differ significantly between stages. Effect sizes for costs and benefits replicate those reported by previous clinical studies. In sum, this study tentatively supports the application of the TTM to the field of entrepreneurship. This model can be used as a framework for the investigation of individual ambivalence towards entrepreneurship. Intervention approaches, such as training in business and administrative practices that are based on participants' answers to open questions, might catalyse entrepreneurial activities.